1998
DOI: 10.1017/s0031182098002698
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an aspartic proteinase precursor from the egg of a hard tick, Boophilus microplus

Abstract: An aspartic proteinase precursor, herein named BYC (Boophilus Yolk pro-Cathepsin) was isolated from eggs of the hard tick, Boophilus microplus. As judged by electrophoresis on sodium dodecyl sulfate polyacrylamide slab gel (SDS-PAGE), purified BYC presented 2 bands of 54 and 49 kDa, bearing the same NH2-terminal amino acid sequence. By Western blot analysis, BYC was also found in the haemolymph, indicating an extraovarian site of synthesis. Several organs were incubated in culture medium with [35S]methionine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
9

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 21 publications
3
52
0
9
Order By: Relevance
“…A previous report has shown that acidification, and the consequent activation of an acid aspartic proteinase, is required for yolk degradation in the cattle tick Boophilus microplus (Logullo et al 1998). In this work we report the presence of a (cathepsin L-like) cysteine endopeptidase, which is associated with vitellin, in eggs of B. microplus and that probably has a role in the VT degradation during B. microplus embryogenesis.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…A previous report has shown that acidification, and the consequent activation of an acid aspartic proteinase, is required for yolk degradation in the cattle tick Boophilus microplus (Logullo et al 1998). In this work we report the presence of a (cathepsin L-like) cysteine endopeptidase, which is associated with vitellin, in eggs of B. microplus and that probably has a role in the VT degradation during B. microplus embryogenesis.…”
Section: Introductionsupporting
confidence: 53%
“…Ticks fed on BYCvaccinated bovines presented functional bovine immunoglobulins circulating in haemolymph (Da Silva Vaz Jr et al 1996). Moreover, cattle vaccinated with BYC presented a partially protective immune response against B. microplus infestation, mainly due to a decreased number of fertile eggs (Da Silva Vaz Jr et al 1998). Considering that VT degradation results from the activity of both enzymes (BYC and VTDCE), VT degradation would be even more impaired if, in addition to antibodies against BYC, bovine antibodies against VTDCE could also be raised.…”
Section: Discussionmentioning
confidence: 99%
“…Newly laid eggs are therefore able to initiate VT degradation. In vitro, measurements of hydrolase activities and yolk degradation using fresh eggs have been investigated by many groups (Nussenzveig et al, 1992;Logullo et al, 1998;Sorgine et al, 2000;Fialho et al, 2002). However, even though freshly laid eggs carry all the yolk mobilization machinery, the massive yolk proteolysis does not occur in vivo immediately after the egg is laid, but starts at a certain time later, during early embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…3C and 4). We previously described another aspartic proteinase, also isolated from Boophilus eggs, called BYC (10). However, none of BYC sequences were identified in THAP cDNA, confirming that BYC and THAP are in fact different proteins.…”
Section: N-cbz-fr-mca (24) Nd N-t-boc-grr-mca (24)mentioning
confidence: 97%